Perbandingan Efektifitas Susu Sapi Cair Kemasan dan Keju Cheddar Kemasan dalam Membantu Menaikkan pH Saliva - Haniyah Atsila Nasri; Lendrawati Lendrawati; Bambang Ristiono (Faculty of Dentistry Universitas Andalas, 2020)
Objective: Oral acidity level that can be assessed from salivary pH is one of indicator for oral health. Diet can change the pH level of saliva, in which low salivary pH caused demineralization of dental email. Milk and cheese have been proven to increase salivary pH because of anticariogenic activity due to the content of casein, calcium, and casein phosphopeptides. This study was aimed to compare the effectivity of packaged cow’s milk and packaged Cheddar cheese to increase salivary pH.; Method: This study was an experimental study with pretest-posttest design. Samples were 35 students in Dentistry of Andalas University, which corresponding to inclusion criteria consumed 125ml packaged cow’s milk and 17gr packaged cheddar cheese in 1 minute on two different days. Salivary pH was measured at time intervals of 5 minutes after consuming soft drink, 5, 10, 15, and 30 minutes after consuming packaged cow’s milk and packaged Cheddar cheese. The data was analyzed by using Wilcoxon and Mann-Whitney statistic test; Result: Wilcoxon test result showed no significant difference in packaged cow’s milk group (p>0,05), and there was a significant difference in packaged cheddar cheese group (p<0,05). Mann-Whitney test result showed a significant difference at 5 and 10 minutes posttest between two groups (p<0,05); Conclusion: There was significant difference in salivary pH between two groups. Packaged cheddar cheese showed significant difference in salivary pH after consumption than packaged cow’s milk.